Environmental quality integrated indicator applied to the management of the Jiquiriçá river watershed, BA, Brazil - Raquel Maria de Oliveira; Neylor Alves Calasans Rego; José Wildes Barbosa dos Santos; Max de Menezes; Jadson Luiz Simões Rocha (Revista Ambiente & Água, 2010)
In this work social, economic and environmental aspects were studied using the concept of programming by commitment, with the objective of structuring an integrated indicator capable of estimating the degree of the environmental quality of the Jiquiriça river basin, BA, composed by the indicator of environmental salubrity, water quality and soil’s protection. For the determination of the environmental salubrity indicator, data of the following variables were collected: existence of treated water supply, disposition and treatment of solid residues, diseases vectors control, the existence of the Agenda 21, socioeconomics data and indices of human development for each municipal district located in the area of the watershed. The indicator of the water quality was structured based on the analysis of water samples collected in eight sampling points along Jiquiriçá river and determined by seven parameters. The indicator of soil’s protection was based on the analysis of maps obtained according to the weight of each steepness and land use class. Results indicate that the watershed is in a poor equilibrium condition and suggest the need for structural investments as well as changes in public polices. The methodology used was efficient for this watershed management and could be used as tool for the environmental planning of the region, once it can be adapted to several situations depending on the data availability.